(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Nanomaterials research has witnessed an exponential growth during the decade. In the nanometric range, metallic and small band gap semiconducting materials exhibit fascinating quantum phenomena. Large band gap materials such as oxides stabilize in their high temperature phases and exhibit enhanced surface phenomena like catalysis and reduced reaction barriers for solid-state reactions[1-2]. Indeed, in the nanometric range, materials may be expected to behave quite differently from both molecular and bulk states since the ratio of the number of surface atoms to the number of bulk atoms is quite high. As a consequence of this increased ratio the number of valence unsatiated atoms in the nanoparticle becomes significant. There is thus a curiosity to understand the behaviour of materials in the nanolength scale and if possible to exploit the new properties exhibited by materials purely as a consequence of the smallness of size. Nano oxide materials have found wide range applications particularly as catalysts and as starting materials for making advanced structural ceramics. During sintering and shaping of oxidic materials for practical applications, use of nano sized particle as starting materials can be of great advantage because of the availability of large surface areas of the nanoparticles.